1983
DOI: 10.1152/jn.1983.50.6.1343
|View full text |Cite
|
Sign up to set email alerts
|

Fast ballistic arm movements triggered by visual, auditory, and somesthetic stimuli in the monkey. I. Activity of precentral cortical neurons

Abstract: Single-unit recordings from motor cortex (area 4) were obtained in two monkeys trained to perform simple flexion and extension movements of the arm in response to somesthetic, visual, and auditory signals. All neurons tested showed movement-related responses that were identical for equivalent movements irrespective of the modality of the triggering stimulus. Progressively longer reaction times were always associated with progressively longer latencies of unit responses. When visual and auditory stimuli were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
51
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 0 publications
10
51
2
Order By: Relevance
“…This phenomenon is well established (e.g., Todd, 1912) and has been reported in a wide range of experimental paradigms (e.g., Koene & Zhaoping, 2007;Mohr, Endrass, Hauk, & Pulvermuller, 2007;Schroter, Ulrich, & Miller, 2007;Gondan, Lange, Rösler, & Röder, 2004;Iacoboni & Zaidel, 2003;Forster, Cavina-Pratesi, Aglioto, & Berlucchi, 2002;Lamarre, Busby, & Spidalieri, 1983). These paradigms can be classified along several criteria: (a) spatial origin of the signals (same or different locations), (b) modality of the signals (visual, auditory, or haptic), (c) number of relevant modalities (one or two), and (d) depth of signal processing necessary to determine the appropriate motor response (onset, feature contrast, or target identity).…”
Section: Introductionmentioning
confidence: 61%
“…This phenomenon is well established (e.g., Todd, 1912) and has been reported in a wide range of experimental paradigms (e.g., Koene & Zhaoping, 2007;Mohr, Endrass, Hauk, & Pulvermuller, 2007;Schroter, Ulrich, & Miller, 2007;Gondan, Lange, Rösler, & Röder, 2004;Iacoboni & Zaidel, 2003;Forster, Cavina-Pratesi, Aglioto, & Berlucchi, 2002;Lamarre, Busby, & Spidalieri, 1983). These paradigms can be classified along several criteria: (a) spatial origin of the signals (same or different locations), (b) modality of the signals (visual, auditory, or haptic), (c) number of relevant modalities (one or two), and (d) depth of signal processing necessary to determine the appropriate motor response (onset, feature contrast, or target identity).…”
Section: Introductionmentioning
confidence: 61%
“…The extent to which nonhuman primates, specifically macaque monkeys, exhibit an RSE in their manual RTs (RTs) to auditory-visual multisensory stimuli is unresolved and was the focus of the present study. Prior research in monkeys observed an RSE only for manual RTs when stimuli were presented asynchronously, although it is noteworthy that such was not statistically validated (Miller, Ulrich, & Lamarre, 2001;Lamarre, Busby, & Spidalieri, 1983). By contrast, studies in humans have successfully used synchronously presented stimuli to elicit an RSE (e.g., Cappe, Thut, et al, 2009;Romei et al, 2009;Martuzzi et al, 2007;Romei, Murray, Merabet, & Thut, 2007;Molholm et al, 2002;Giard & Peronnet, 1999).…”
Section: Introductionmentioning
confidence: 93%
“…The assessment of whether RT facilitation exceeded levels predicted by probability summation allowed us to determine whether integrative processes need to be invoked to account for behavioral improvements. Given the pattern of results obtained by Miller et al (2001) and Lamarre et al (1983), who failed to observe an RSE with synchronously presented and suprathreshold auditory and visual stimuli, and given the fact that studies in humans routinely obtain an RSE with synchronously presented auditory-visual stimuli, we parametrically varied the efficacy of auditory stimuli. We hypothesized that multisensory stimulus presentation facilitates detection near threshold and shortens RT as compared with unisensory stimulus presentation (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Another difference is the presence or absence of a selective relationship to a movement initiated differently. In MI neurons, the movement-related activity is similar, regardless of whether the movement is triggered by a visual, auditory or tactile signal [32,68]. In contrast, the activity of SMA neurons are often selective.…”
Section: Neuronal Activity In the Sma Appear Different From That In Tmentioning
confidence: 99%